Lacoste, Pablo (compilador) Argentina – Chile y sus vecinos (Tomo I). Mendoza, Editora Andina Sur Caviar Bleu, 2005, 441 páginas. ISBN: 987 – 21358 – 6 – X - Orellana Yáñez, José (Estudios Avanzados, 2012)
Lacoste, Pablo (compilador) Argentina – Chile y sus vecinos (Tomo I). Mendoza, Editora Andina Sur Caviar Bleu, 2005, 441 páginas. ISBN: 987 – 21358 – 6 – X